Comparison between isometric analysis and randomized complete block design and its application for the purpose of determining the best method for controlling the red flour beetle. (Journal of the College of Basic Education, 2022)
The research includes a study of three methods to combat the red flour beetle. These methods are airtight storage, exposure to sunlight, and the addition of vegetable powder (black pepper), and through the use of two methods, symmetrical analysis and random complete sectoral analysis. Comparing them, we find that each of the two analyzes confirms that the method Exposure to sunlight is the best way to control the red flour beetle